Prevalence of hypertension and variation in blood pressure among school children in rural area of Wardha - Rohan Raosaheb Patil; Bishan Swarup Garg (Wolters Kluwer Medknow Publications, 2014)
Objective: To study the prevalence of hypertension and variation in blood pressure (BP) level among school children in rural India. Design: A cross-sectional study was conducted during the period from April 2010 to March 2012. Setting: Participants comprised of 958 school children (in the age group of 6-16 years) from 83 schools covered by three randomly selected primary health centers. Materials and Methods: After obtaining informed consent from the school principal, a pretested questionnaire was administered and anthropometric measurements were taken. Hypertension was defined as systolic blood pressure (SBP) and/or diastolic blood pressure (DBP) ≥95 th percentile for age, gender, and height measured on three distinct occasions. Results: Overall, prevalence of hypertension and was found to be 29 (3.0%). The proportion of hypertension among males was 13 (2.8%) against 16 (3.2%) in females. Overall mean SBP level was 97.2 mmHg and DBP level was 62.1 mmHg. Conclusion: SBP and DBP found to be correlated with the body mass index, waist circumference, which identifies the need of proper dietary changes at individual and family level. Constructed nomogram for study participants show lesser SBP and DBP values for 90 th and 95 th percentiles among Indian children when compared to NHLBP guidelines. This suggests lesser BP cut-off needed to identify maximum hypertensive population among Indian children.